Adenoma Detection is Increased in the Setting of Melanosis Coli. Issue 4 (April 2018) - Blackett, John W.; Rosenberg, Richard; Mahadev, Srihari; Green, Peter H.R.; Lebwohl, Benjamin
Abstract : Goals: To compare the adenoma detection rate (ADR) during colonoscopy in patients with melanosis coli against matched controls without melanosis. Background: Melanosis coli is a colonoscopic finding in which the colon wall appears darkly pigmented, most often due to extended laxative use, and is considered benign. The pigmentation spares adenomas, which should therefore be more readily detectable in melanosis coli. Study: We identified all patients with melanosis on colonoscopy at our institution over a 5-year period. We matched each patient with 2 controls by age, gender, and endoscopist. We compared the prevalence of adenomas between groups, and used multivariable analysis, adjusting for procedure indication and bowel preparation quality, to determine the independent association of melanosis with adenoma detection. Results: At least 1 adenoma was detected in 34.7% of melanosis patients and 26.5% of controls [odds ratio (OR)=1.52; 95% confidence interval (CI), 1.04-2.24; P =0.03]. On multivariable analysis, the presence of melanosis remained associated with increased adenoma detection (OR=1.56; 95% CI, 1.05-2.33; P =0.03). Melanosis patients were more likely to have an adenoma ⩽5 mm (OR=1.62; 95% CI, 1.04-2.51; P =0.03), but not adenomas 6 to 9 mm or ≥10 mm. Conclusions: Melanosis coli is associated with a significant increase in ADR during colonoscopy compared with controls. The increased visibility of adenomas given their contrast with the pigmented background is a likely explanation. Future efforts to identify bowel preparation agents that can induce a similar effect could improve ADRs during colonoscopy.